2017
DOI: 10.1038/nplants.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the SHR–SCR heterodimer bound to the BIRD/IDD transcriptional factor JKD

Abstract: The plant-specific GAI-RGA-and-SCR (GRAS) family proteins play critical roles in plant development and signaling. Two GRAS proteins, SHORT-ROOT (SHR) and SCARECROW (SCR), cooperatively direct asymmetric cell division and the patterning of root cell types by transcriptional control in conjunction with BIRD/INDETERMINATE DOMAIN (IDD) transcription factors, although precise details of these specific interactions and actions remain unknown. Here, we present the crystal structures of the SHR-SCR binary and JKD/IDD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 46 publications
2
65
0
Order By: Relevance
“…). However, GRAS domains lack the SAM‐binding motifs, which are conserved in SAM‐MT members and no binding was observed for SAM, S ‐adenosyl homocysteine, or the product monomethyl‐L‐lysine in our binding assays using isothermal titration calorimetry (ITC) , suggesting that the GRAS domains lack methyltransferase activity.…”
Section: Gras Domain Structurementioning
confidence: 86%
See 2 more Smart Citations
“…). However, GRAS domains lack the SAM‐binding motifs, which are conserved in SAM‐MT members and no binding was observed for SAM, S ‐adenosyl homocysteine, or the product monomethyl‐L‐lysine in our binding assays using isothermal titration calorimetry (ITC) , suggesting that the GRAS domains lack methyltransferase activity.…”
Section: Gras Domain Structurementioning
confidence: 86%
“…More definitive evidence showing oligomerization of GRAS proteins has been obtained using hydrodynamic analyses such as analytical ultracentrifugation (AUC) with purified protein samples (Fig. ) . The analyses using AUC clarified the stable monodispersed states of Arabidopsis GRAS proteins in solution with estimated molecular masses showing that SCL5 exists as a monomer, while SCL3 exists as a homodimer, and SHR‐SCR exist as a 1 : 1 heterodimer.…”
Section: Monomer‐dimer Equilibrium In Solutionmentioning
confidence: 95%
See 1 more Smart Citation
“…Yeast-2-hybrid experiments have shown that SHR and SCR can bind to JACKDAW, as well as to its closest homologs BALD IBIS, and MAGPIE [18,20]. Moreover, a recent manuscript describes the crystal structure of the SHR-SCR-JKD and SHR-SCR-MGP complexes [21]. These results indicate that SHR-SCR cannot bind to DNA alone, but require formation of a complex with an IDD TF.…”
Section: Identifying New Nodes In the Grn Underlying Asymmetric Cell mentioning
confidence: 99%
“…For example, Hirano et al 1 have investigated the interactions that lie at the heart of root patterning by determining the structure of a heterodimer of SCARECROW (SCR) and SHORT-ROOT (SHR), both on its own and when bound to the transcription factor JACKDAW (JKD). These specific interactions are important for determining cell fates in the developing root, but SCR and SHR are also representatives of a large family of transcriptional regulators known as GRAS proteins due to their homologous GRAS domains.…”
mentioning
confidence: 99%